Challenges in conserving forest ecosystems through coffee certification: a case study from southwestern Ethiopia - Arai, Yuki; Hundera, Kitessa; Yoshikura, Toshihide (Frontiers in Environmental Science, 2023)
Certification schemes, aimed at simultaneously promoting ecologically sustainable agriculture and improving livelihood, are being utilized at a global scale. Among such certification schemes, the Rainforest Alliance is known as one of the most widely used environmental certification programs throughout the world. Previous studies have compared the ecological impacts of certified and noncertified farmlands, or evaluated the economic outcomes of certification. However, few studies have assessed the long-term impacts of the certification scheme. This paper attempts to analyze the longterm outcomes of the Rainforest Alliance certification program through a case study of coffee farming practices in southwestern Ethiopia. We conducted in-depth qualitative interviews with key informants who were deeply involved in the certification program, together with field observations and secondary data collection. The results of the assessment indicated that some areas of the certified coffee forests have been deforested or ecologically degraded and that the Rainforest Alliance program requirements were not uniformly applied. The possible causes include rapid population increase, government policies promoting intensive coffee production, presence of members who did not participate in the certification program, a lack of conservation incentives, and loopholes in the auditing process. To determine the overall success of the Rainforest Alliance certification program would require: monitoring of population growth rates and providing alternative livelihood opportunities, promoting collaboration between environmental and agricultural government authorities, conducting a more stringent on-site inspection, and to provide direct incentives for environmental conservation to all farmers living in or near the certified areas.